PERAN GURU DALAM PENGEMBANGAN BAHASA LISAN PADA ANAK USIA 5-6 TAHUN DI PAUD KECAMATAN BELIMBING - Rini, .; ., Fadillah,; ., Lukmanulhakim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractTeachers' Role in Language Development of spoken language 5- 6 Years Old School Early Childhood Education Belimbing districts that teachers have not maximized the involvement of children so that teachers implement learning by methods such as writing, submission of materials, question and answer, basically just pressing on the concept of textual achievement alone but not the growth or development of learning activities, and make children become lazy and bored in following the lessons, especially during the development of oral language of children. Based on the results of data analysis shows that the role of teachers as a motivator in the development of spoken languageof children aged 5-6 years in early childhood education Belimbing District is good with the amount of 70.97%. the role of teachers as a mediator in the development of spoken languageof children aged 5-6 years in early childhood education Belimbing District is good with the amount of 65.52%. The role of teachers as facilitators in the development of spoken language children aged 5-6 years in early childhood education Belimbing District is good with number 48.39%. The role of teachers as evaluators in the development of spoken languagechildren aged 5-6 years in early childhood education District Belimbing i is good. with a total of 87.1%. It is expected that in the implementation of the teacher's performances more carefully on the techniques or methods used. Keywords: Teacher Role, spoken language, Early Childhood Education